2013
DOI: 10.1039/c3ra40516h
|View full text |Cite
|
Sign up to set email alerts
|

Guest molecule dynamics and guest-specific degassing phenomenon of binary gas hydrate investigated by terahertz time-domain spectroscopy

Abstract: Guest molecule dynamics and guest-specific degassing phenomenon of binary gas hydrate investigated by terahertz time-domain spectroscopy3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The state of the sample at 263 K should be hexagonal ice because there is no known measurable intermediate or activated states during the dissociation process from hydrate to ice or water. We previously reported that the presence of CH 4 , H 2 , and O 2 molecules in the THF sII hydrate did not affect the THz electric fields in the time domain . The notable change in the electric fields indicates that THz light is transmitted faster through ice than through the hydrate, and thus ice has a smaller refractive index than gas hydrates.…”
Section: Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The state of the sample at 263 K should be hexagonal ice because there is no known measurable intermediate or activated states during the dissociation process from hydrate to ice or water. We previously reported that the presence of CH 4 , H 2 , and O 2 molecules in the THF sII hydrate did not affect the THz electric fields in the time domain . The notable change in the electric fields indicates that THz light is transmitted faster through ice than through the hydrate, and thus ice has a smaller refractive index than gas hydrates.…”
Section: Results and Discussionmentioning
confidence: 96%
“…Different combinations of the guest molecules of CH 4 and CO 2 will then have a superimposed effect on the THz absorption. Considering the changes in the amplitude spectra observed for sII hydrates with different guest molecules, the guest contribution in THz-TDS may be emphasized . Although free molecules of both methane and carbon dioxide do not have a permanent dipole moment, it was recently revealed that methane showed faint absorption in the THz region due to centrifugal distortion effects .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36) Although several studies of ice based on THz technology have been reported, 13,14,37,38) there are few studies based on gas hydrates in the THz regime. 29,30,39) Investigating the optical and dielectric properties of gas hydrates at THz frequencies should provide useful information. In this paper, we report the modeling of dielectric parameters of gas hydrate including non-polar guest molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, terahertz (THz) spectroscopy has a function such that it is highly sensitive to hydrogen-bonded functional groups and can more favorably be used to probe the dynamics of water molecules comprising the cage frameworks in clathrate hydrates. Takeya et al measured the optical properties of ice, THF hydrate, propane hydrate, and SF 6 hydrate in the THz region. Additionally, in our previous works, we explored the guest dynamics of gaseous guest molecules and the physical properties of semiclathrate hydrates using THz-time-domain spectroscopy (TDS) . In this study, we attempted to use THz-TDS to closely examine the formation behavior of tetrahydrofuran (THF) hydrate in KHI-dosed PVP.…”
Section: Introductionmentioning
confidence: 99%